(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
On 22 March 1904, the Protestant newspaper Der Reichsbote published an anonymous letter, the author of which was later identified as Jakob Irle, a missionary with the Rhenish Missionary Society. The article exposes as lies and propaganda the reports in the German press of alleged atrocities committed by the OvaHerero, especially against women, and is all the more impressive for the list of named, verifiable alleged examples it debunks. Irle places the causes of the OvaHerero’s armed resistance firmly on the German colonists’ side and apportions no blame to the OvaHerero. In so doing, he openly and directly contradicts the position taken by most of the German press on the cause of the war. Irle interprets the anti-colonial resistance as a reaction to the Germans’ violence, arbitrariness and ’lechery’ against OvaHerero, which were prevalent long before the war broke out. Irle’s contribution received a lot of media attention at the time, triggering heated discussions, outrage and criticism, and is thus an important and often referred to document in the colonial history of South West Africa, which is, however, difficult to access today.